Complex PTSD and Forced Migration of Children and Adolescents from Latin America - Franco, Fabiana (Journal of Psychological Research, 2022)
In order to provide culturally competent care to children and adolescents that have been subject to forced migration, clinicians must first understand the unique trauma these individuals experienced. Victims of forced migration frequently experience trauma pre-displacement, typically resulting from the same factors that led to the forced migration. They then often experience trauma during the migration itself and post-migration as they settle in a new environment, sometimes without their families if they are unaccompanied minors. An increased risk of developing complex PTSD (C-PTSD) correlates with the number of adverse childhood experiences (ACEs) such as those experienced by children and adolescents that experience forced migration. Understanding the nuances of these traumas and their specific manifestations for the individual child or adolescent is critical for effective behavioral health support. Trauma signature (TSIG) analysis offers clinicians a method to understand the relationship between traumatic events and the physical and psychological consequences to best support these victims.